Health economics of snakebite envenomation: A sub-Saharan African perspective - Ayesiga, Innocent; Gmanyami, Jonathan Mawutor; Akaka, Alex; Kubwimana, Olivier; Ternor, Joshua Naatey; Hashim, Ukasha Musa; Gyabaah, Gertrude Ahenewaa; Turzin, Justice Kwadwo; Kahwa, Ivan (Transactions of The Royal Society of Tropical Medicine and Hygiene, 2025)
Sub-Saharan Africa (SSA) is affected by the high direct and indirect costs of snakebite envenomation. With >30% of global mortality, different economic barriers still exist, and effective strategies must be employed to avert the burden and promote quality of life. With the WHO target of reducing the number of snakebites by one-half by 2030, different aspects concerning snakebite envenomation economics must be evaluated, and potential strategies must be developed. Strategies such as exploring the different snakebite prevention interventions, and the costs associated with these interventions, must be prioritized through extensive research and targeted surveys. Information obtained from these surveys can be used to draft effective policies to minimize snakebite envenomation incidence, reduce the economic burden associated with envenomation and improve the quality of life of people at risk. In this narrative review, we evaluate the different aspects concerning the health economics of snakebite envenomation and explore the financial capacity of SSA countries to mitigate envenomation. Additionally, we propose multiple steps that could be undertaken to mitigate the financial burden of envenomation in SSA. Furthermore, we propose critical research strategies to minimize direct and indirect costs arising from snakebite envenomation in the region.
Keywords: Envenomation costs; Envenomation economics; Snakebite; Snakebite economic burden